Tumbuhnya Solidaritas Sosial Di Tengah Banjir Bandang Semarang Tahun 1990 - Harini, Okti Ria; Wijayati, Putri Agus (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This article aims to revisit the emergence of social awareness among the people of Semarang during the flood disaster of 1990. That year, the flood was caused by both natural and non-natural factors. One of the triggers was heavy rainfall, which caused the Kaligarang River to overflow and flood the areas of Sampangan, Simongan, and Bongsari. These three areas suffered significant losses, both material and non-material. In addition, the flood, categorized as a large-scale disaster, or as the community referred to it, a "flash flood," which occurred at 2:00 AM local time, not only shocked the people but also had an extraordinary impact on various aspects. One of the most felt impacts was the social aspect, as many residents lost their homes and belongings. This study uses historical research methods, starting with the collection of primary sources, both written and oral. Written primary sources were mainly found in the Suara Merdeka newspaper from the same year the flood occurred. Meanwhile, oral primary sources were gathered through interviews with three informants. The research findings revealed that the flood in Semarang on January 26, 1990, was able to foster social awareness among the city's residents. This was a condition rarely seen before, as the city's citizens were more individualistic. However, the 1990 flood helped cultivate a sense of solidarity among the city's residents. This solidarity was not only from the local community but also from various groups such as the Health Department, social organizations, corporations, religious organizations, and students. The active participation of many parties created social bonds that became key in forming survival patterns in the city. Keywords : Social Solidarity, Flash Flood, Semarang City